Virtual reality modulates the control of upper limb motion in one-handed ball catching - Hirofumi Ida; Kazunobu Fukuhara; Takahiro Ogata (Frontiers Media S.A., 2022)
There remains a question about whether and to what extent perception-action coupled response in virtual reality are equal/unequal to those in the real world or physical reality. The purpose of this study was to identify the differences in the environmental effect of virtual presentation on the motor responses of a one-handed ball catching. Thirteen healthy participants were instructed to catch an approaching ball projected at three speeds in a real laboratory room and in a room-sized virtual reality system (CAVE) that simulated those real situations with two- or three-dimensional display settings. The results showed that the arm movement time, which denotes the duration of arm-raising motion (shoulder flexion), was significantly longer in the virtual reality than that in the physical reality at the fast ball speed condition. The shoulder flexion velocities, calculated as the average angular velocity of shoulder flexion over the arm movement time, were significantly lower in the virtual reality than in the physical reality at the medium and fast ball speed conditions. The electromyography onsets, derived from anterior deltoid, biceps brachii, and flexor carpi radialis muscles of the catching arm, appeared before and significantly closer to the initiation of arm raising in the two-dimensional virtual reality than both in the physical reality and in the three-dimensional virtual reality. The findings suggest that simulation of virtual reality may induce a modulation in the motor responses of the catching arm, which is different from natural motion that appeared in the real world. On the contrary, the effect of ball speed generally found in real setting was maintained in the current CAVE experiment.